Pengaruh Kompensasi Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada Hotel Jazz Di Kota Palu - Ni Wayan Yunita; Syamsuddin R; Fadila Almahdali (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study was to identify and analyze the effect of compensation and leadership style on employee performance at the Jazz Hotel in Palu City. By using 51 respondents. Data analysis using multiple linear regression analysis. The results of the analysis show that compensation and leadership style simultaneously have a significant effect on the performance of Hotal Jazz in Palu City. Compensation has a significant effect on the performance of Hotal Jazz in Palu City. Leadership style has a significant effect on the performance of Hotal Jazz in Palu City.